Canine separation-related behaviour at six months of age: Dog, owner and early-life risk factors identified using the ‘Generation Pup’ longitudinal study - Fiona C. Dale; Charlotte C. Burn; Jane Murray; Rachel Casey (Animal Welfare)
Separation-related behaviours (SRBs) in dogs (Canis familiaris) often indicate poor welfare. Understanding SRB risk factors can aid prevention strategies. We investigated whether early-life experiences and dog-owner interactions affect SRB development. Using a longitudinal study, we conducted exploratory analyses of associations between potential risk factors and SRB occurrence in six month old puppies (n = 145). Dogs were less likely to develop SRBs if owners reported that, at ≤ 16 weeks old, puppies were restricted to crates/rooms overnight and had ≥ 9 h of sleep per night. Puppies with poor house-training at ≤ 16 weeks were more likely to show SRBs, as were those trained using dog treats or novel kibble versus other rewards. Puppies whose owners used more punishment/aversive techniques when responding to ‘bad’ behaviour had increased odds of SRBs at six months versus other puppies. Puppies whose owners reported ‘fussing’ over their dogs at six months in response to ‘bad’ behaviour upon their return, versus those whose owners responded in other ways, were six times more likely to display SRBs. Other factors, including dog breed, sex and source, showed no significant association with SRB occurrence. Thus, SRB development might be prevented by enabling sleep for ≥ 9 h in early life, providing enclosed space overnight, refraining from aversive training of puppies generally, and avoiding fussing over puppies in response to unwanted behaviour following separation. These recommendations derive from correlational longitudinal study results, so analysis of interventional data is required for confirmation regarding effective prevention strategies.